Perlindungan Hukum Terhadap Konsumen Shopee Atas Barang Yang Tidak Sesuai Dengan Deskripsi Produk - Ari Apriatman Molle; Teng Berlianty; Agustina Balik (Faculty of Law Universitas Pattimura, 2023)
Consumer protection is important considering the speed of science and technology that continues to increase. This study aims to examine legal protection for shopee consumers for goods that do not match the product description and the responsibilities of the shopee party and business actors for consumers who are harmed. The type of research used in this paper is normative legal research. By using the legal approach and the concept approach. Analysis of legal material uses qualitative methods, namely studies related to legal norms contained in laws and regulations and legal norms that exist in society. The qualitative analysis method is carried out by analyzing legal materials based on concepts, theories, laws and regulations, expert opinions, and the views of the authors themselves, then interpretation is carried out to conclude from this research question. The results of this study conclude that legal protection for Shopee consumers is based on the Consumer Protection Act No. 8 of 1999 (UUPK) and the Electronic Information and Transaction Law No. 11 of 2008 (UU ITE) can be seen in the regulation on consumer rights protection. Consumers who are harmed can file a lawsuit that is in line with UUPK and UU ITE so as to provide legal certainty to consumers. The government and society also play an important role through the oversight function. The form of responsibility of the shopee party and business actors for losses suffered by consumers is fully regulated in the terms of use of services available on the shopee shopping site, allowing consumers to report consumer losses, offer Shopee Guarantees, issue refunds to consumers, and protect consumers' personal information and credit cards. . Shopee is fully responsible for consumer losses